An international comparison of deceased donor kidney utilization: What can the United States and the United Kingdom learn from each other?. Issue 5 (21st December 2019) - Ibrahim, Maria; Vece, Gabe; Mehew, Jenny; Johnson, Rachel; Forsythe, John; Klassen, David; Callaghan, Chris; Stewart, Darren
Abstract : In transplant, meaningful international comparisons in organ utilization are needed. This collaborative study between the United Kingdom (UK) and the United States (US) aimed to develop a kidney utilization metric allowing for legitimate intercountry comparisons. Data from the UK and US transplant registries, including all deceased donor kidneys recovered from 2006 to 2017, were analyzed. To identify a potentially comparable kidney utilization rate (UR), several denominators were assessed. We discovered that the proportion of transplanted kidneys from elderly donors in the UK (10.7%) was 18 times greater than that in the US (0.6%). Conversely, en bloc pediatric kidney transplant was more common in the US. Donation after circulatory death utilization has risen in both countries but is twice as prevalent in the UK (39% of transplants) vs the US (20%). In addition, US and UK URs are not directly comparable due to fundamental system differences. However, using a suite of URs revealed practice areas likely to yield the most benefit if improved, such as efforts to increase kidney offer acceptance in the US and to reduce postacceptance discard in the UK. Methods used in this study, including novel intracountry risk‐adjusted UR trend logistic regression analyses, can be translated to other international transplant registries in pursuit of further global learning opportunities. Abstract : This international registry collaborative study explores meaningful comparable metrics for quantifying deceased donor kidney utilization and discusses intercountry differences in characteristics of recovered and transplanted kidneys. See an editorial from Manook and Kirk on page 1221 .